An Investigation of open access publications’ attractiveness among academic researchers from three European countries - Gurau, Calin (Septentrio Conference Series, 2019)
A thriving open access publication (OAP) system represents a sound basis for Open Science development. Unfortunately, it is not yet clear what are the factors determining that academic researchers use OAPs, both as a source of knowledge and relevant references, and as an outlet to present their work to their peers, students and/or the general public. To investigate this topic, we assume an interpretative framework rooted in the institutional theory. Considering the development and evolution of the OAP system as a coherent set of structures, norms and routines, our research aims to (i) identify the factors that determine academic researchers in the business field to become active participants in this system; and (ii) to compare the way in which these factors influence academic researchers’ choices and professional strategies in three different European countries, which are traditionally different in terms of research culture and orientation: France, Romania and the UK. We adopt a research methodology based on semi-structured interviews, as our research objectives require a qualitative approach to identify not only the individual reasons for using the OAP system, but also the influence of the professional environment in shaping these decisions in terms of institutional standards, rules and practices. To collect primary data, we interviewed a total of 42 academics, who are active in both teaching and research in higher education institutions located in France, Romania or the UK (14 respondents from each country). The interviews lasted between 30 and 45 minutes, being conducted either face-to-face or through skype. With the permission of respondents – but under strict confidentiality standards, the interviews were transcribed, coded and analysed. The findings draw a highly complex picture indicating a set of conflicting factors and forces that determine the official perception and use of the OAP system. Although each of the investigated countries has specific features in terms of higher education quality standards and practices, respondents indicated a strong tendency towards uniformization, determined by the global spread of the North American academic system, which directly connects the professional status and evolution of academic researchers to their capacity to publish in peer-reviewed journals that are highly ranked in national or international publications lists (e.g., ISI, ABS, CNRS, FNEGE, etc.). Presently, there are relatively few open access journals included in national/international journal ranking lists, which prevents a widespread use of the OAP system by business academic researchers. Respondents indicated that although they currently use OAPs as a source of knowledge for teaching, they are more reluctant to use them as publication outlets for their research work, or as references in their scholarly publications. This tendency differs between these national education systems, although the general trend indicates a strong convergence of opinions and institutional practices. Overall, the academic publishing landscape can be described as a battlefield between two competing sets of institutions centred around open access and paid access systems, the paid access system still representing the standard for academic quality and professional recognition.